Geospatial analysis of canine leptospirosis risk factors in the central Great Plains region - Raghavan, Ram (Kansas State University, 2012)
Associations of land cover/land use, socio-economic and housing, and hydrological and soil-hydrological variables were evaluated retrospectively as potential risk factors for canine leptospirosis in Kansas and Nebraska using Geographic Information Systems (GIS). The sample included 94 dogs positive for leptospirosis based on a positive polymerase chain reaction test for leptospires in urine, isolation of leptospires on urine culture, a single reciprocal serum titer of 12,800 or greater, or a four-fold rise in reciprocal serum titers over a 2 to 4 week period; and 185 dogs negative for leptospirosis based on a negative polymerase chain reaction test and reciprocal serum titers less than 400. Publicly available geographic datasets representing land cover/land use, socio-economic and housing characteristics, and hydrologic and soil hydrologic themes were analyzed along with geocoded addresses of case/control locations in GIS. Among different land cover/land use variables evaluated, urban areas (high and medium intensity urban areas and urban areas in general) and evergreen forests and forest/woodlands in general were significant risk factors. Among socio-economic and demographic determinants evaluated, houses lacking complete plumbing facilities, poverty status by age (18-64), and living within 2500 meters of a university/college or parks/forests were significant risk factors. Proximity to water features, hydrologic density and frequently flooded areas were identified as significant risk factors for canine leptospirosis among hydrologic and soil-hydrologic variables. Pet owners whose dogs live in such areas or under these circumstances should consider vaccination to prevent canine leptospirosis.
Keywords: Canine leptospirosis; Risk factors; Geographic information systems; Land cover/land use; Remote sensing; Socio-economics; Epidemiology (0766)